Saran Implementasi Sistem ERP Berdasarkan Keuntungan dan Tantangan: Literature Review: Suggestions for ERP System Implementation Based on Benefits and Challenges: Literature Review - Muhammad Syaifuddin, Nur; Zaini, Ahmad; Suriansyah, Muhammad; Puji Widodo, Aris (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2024)
This research is a literature review that aims to investigate the implementation of Enterprise Resource Planning (ERP) systems and provide practical suggestions based on the benefits and challenges associated with ERP systems. ERP is software designed to integrate various functions and departments in a company into one integrated system. ERP implementation can provide benefits such as increased operational efficiency, better monitoring of company performance, and better decision making. However, ERP implementation also presents challenges such as high costs, change resistance from employees, and integration problems with existing systems. This research uses the Systematic Literature Review (SLR) method to identify, assess and interpret findings related to ERP implementation. The results of this research provide practical suggestions, including a focus on key benefits such as increased efficiency, reduced costs, and improved data quality. In addition, companies also need to overcome challenges such as high costs, change resistance, and integration problems. By paying attention to these suggestions, companies can maximize the benefits of implementing an ERP system and improve their operational performance and strategy. Keywords : Advantages, Challenge, Suggestion, Implementation, ERP